2013
DOI: 10.1097/opx.0b013e31828736f3
|View full text |Cite
|
Sign up to set email alerts
|

Symptomatic and Morphological Differences between Choroidal Excavations

Abstract: Symptomatic and morphological differences between focal choroidal excavations suggested anatomical alterations between the photoreceptor tips and the retinal pigment epithelium or location of choroidal excavation as the cause of metamorphopsia. We speculate that the pathogenesis of focal choroidal excavation involves outward traction on the macula caused by choroidal vascular abnormalities because of embryonic developmental failure of the choroid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 8 publications
0
17
0
1
Order By: Relevance
“…In our series, FFA confirmed acute CSCR in 4 eyes. By comparing these 4 eyes with the nonconforming-type cases in the literature [2,3,5,15], the following differences were noted: first, the retinal detachment was always within the excavation in nonconforming cases, while it usually exceeded the excavation in CSCR cases; second, the fine lines of the ELM and the IS/OS at the detached area were slightly above the normal counterparts in CSCR cases, while they were below those of the normal counterparts in nonconforming cases; third, changes in PRE were more common and prominent in CSCR cases; and fourth, CSCR eyes could be either type 1 or 2 (there were more type 2 in our series), while nonconforming-type cases described in previous reports were mostly type 1 [2,3,5,15]. And since recent study found that choroidal thickness was increased in focal choroidal excavation patients if complicated by CSC, so this could be another point that could be helpful in the differentiating [12].…”
Section: Discussionmentioning
confidence: 99%
“…In our series, FFA confirmed acute CSCR in 4 eyes. By comparing these 4 eyes with the nonconforming-type cases in the literature [2,3,5,15], the following differences were noted: first, the retinal detachment was always within the excavation in nonconforming cases, while it usually exceeded the excavation in CSCR cases; second, the fine lines of the ELM and the IS/OS at the detached area were slightly above the normal counterparts in CSCR cases, while they were below those of the normal counterparts in nonconforming cases; third, changes in PRE were more common and prominent in CSCR cases; and fourth, CSCR eyes could be either type 1 or 2 (there were more type 2 in our series), while nonconforming-type cases described in previous reports were mostly type 1 [2,3,5,15]. And since recent study found that choroidal thickness was increased in focal choroidal excavation patients if complicated by CSC, so this could be another point that could be helpful in the differentiating [12].…”
Section: Discussionmentioning
confidence: 99%
“…12 Kumano ve ark., ekskavasyon alanında vasküler anormallik olduğunu ve hiperreflektan dokunun Bruch membranı ve suprakoroidal lamina arasındaki anormal adezyonlar olabileceğini bildirmişlerdir. 13 Benzer hiperreflektan doku görünümü olgu 3'te de mevcuttur. Ayrıca, olgu 1 ve 2'nin FFA'sında lezyon alanına uyan bölgedeki koroid floresanın çevresine göre daha hipofloresan olarak izlenmesi altta yatan koroid hipoperfüzyonundan ya da oluşan skar dokusunun koroidal vasküler yapıyı bozmasından kaynaklanıyor olabilir.…”
Section: Discussionunclassified
“…However, it is considered that FCE could be an embryonic developmental disorder or an acquired pathology. Some authors hypothesize that FCE is a congenital malformation while as others theorize that it might due to the failure of chorioretinal development in the embryonic stage, micro staphyloma, congenital focal choroidal dysplasia, focal choroidal atrophy caused by congenital or acquired choroiditis [2,3,11,[26][27][28][29][30][31][32][33] . Focal choroidal excavation often does not appear in mono/ polychromatic fundus photography, fundus angiography or ophthalmoscopy and it might be only detected using OCT.…”
Section: Discussionmentioning
confidence: 99%
“…In 2011, this tomographical entity was called as FCE by Margolis et al [2] . FCE is defined as a focal area of intrachoroidal concavity in the macula detected in OCT in an eye with preserved visual acuity and normal fundus without a posterior staphyloma or scleral ectasia, a history of trauma, inflammatory/ infectious or vascular disease in retina or choroid [2][3][4][5][26][27][28][29][30][31][32][33] . Although the FCE is a relatively stationary lesion, it can cause the CNV [6][7][8] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation